2015
DOI: 10.5527/wjn.v4.i2.245
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hypogonadotropic male hypogonadism: Case-based scenarios

Abstract: The aim of this study is to review four case-based scenarios regarding the treatment of symptomatic hypogonadism in men. The article is designed as a review of published literature. We conducted a PubMed literature search for the time period of 1989-2014, concentrating on 26 studies investigating the efficacy of various therapeutic options on semen analysis, pregnancy outcomes, time to recovery of spermatogenesis, as well as serum and intratesticular testosterone levels. Our results demonstrated that exogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
(34 reference statements)
0
25
0
Order By: Relevance
“…One of the reasons might be that HFD mouse model has yet not attained the morbid obesity extent. Under physiological conditions, the levels of intratesticular testosterone (ITT) in male were some 40‐ to 100‐fold higher than those in the circulation . So, the concentrations of ITT were measured subsequently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons might be that HFD mouse model has yet not attained the morbid obesity extent. Under physiological conditions, the levels of intratesticular testosterone (ITT) in male were some 40‐ to 100‐fold higher than those in the circulation . So, the concentrations of ITT were measured subsequently.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, the levels of intratesticular testosterone (ITT) in male were some 40-to 100-fold higher than those in the circulation. [39][40][41] The Ppif +/+ mice and Ppif −/− mice were bred by sexual hybridization of Ppif ± male and female mice. Ppif −/− mice were born at the expected Mendelian frequency, developed normally, and did not have any detectable phenotype and viability anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with obesity, poorly controlled diabetes, or opioid usage should be counseled on weight loss, diet, exercise, and drug abuse before starting testosterone replacement therapy (TRT). Formal weight loss programs have not only shown that the percentage of weight loss correlated with increased T levels, but parameters related to fertility including sperm motility and morphology also improved (38). While there is evidence that T may reduce HbA 1C , lower BMI, and reduce waist circumference other studies have not shown any change in HbA 1C with testosterone compared to placebo (39).…”
Section: Treatment Options For Adolescent and Young Adulthood Men With mentioning
confidence: 99%
“…Although the exact mechanism of action and production site in males are not fully understood, it is known that hCG mimics the effects of LH and stimulates the Leydig cells in the testicles to produce endogenous testosterone [3585960]. Additionally, studies have shown that low-dose hCG can be used with TRT to maintain high levels of intra-testicular testosterone while men are being treated for hypogonadism [5261]. While hCG is effective in increasing testosterone, various studies have shown that it is also efficacious in inducing spermatogenesis [6263].…”
Section: Alternatives To Testosterone Therapy In Patients Who Wish Tomentioning
confidence: 99%